Ty3 GAG3 and POL3 genes encode the components of intracellular particles. - Hansen, L J (1992)
Ty3 is a Saccharomyces cerevisiae retrotransposon that integrates near the transcription initiation sites of polymerase III-transcribed genes. It is distinct from the copialike Ty1 and Ty2 retrotransposons of S. cerevisiae in both the sequences of encoded proteins and gene order. It is a member of the gypsylike family of retrotransposons which resemble animal retroviruses. This study was undertaken to investigate the nucleocapsid particle of a transpositionally active gypsylike retrotransposon. Characterization of extracts from cells in which Ty3 expression was induced showed the presence of Ty3 nucleoprotein complexes, or viruslike particles, that migrated on linear sucrose gradients with a size of 156S. These particles are composed of Ty3 RNA, full-length, linear DNA, and proteins. In this study, antibodies raised against peptides predicted from the Ty3 sequence were used to identify Ty3-encoded proteins. These include the capsid (26 kDa), nucleocapsid (9 kDa), and reverse transcriptase (55 kDa) proteins. Ty3 integrase proteins of 61 and 58 kDa were identified previously (L. J. Hansen and S. B. Sandmeyer, J. Virol. 64:2599-2607, 1990). Reverse transcriptase activity associated with the particles was measured by using exogenous and endogenous primer-templates. Immunofluorescence studies of cells overexpressing Ty3 revealed cytoplasmic clusters of immunoreactive proteins. Transmission electron microscopy showed that Ty3 viruslike particles are about 50 nm in diameter. Thus, despite the unusual position specificity of Ty3 upstream of tRNA-coding regions, aspects of the Ty3 life cycle are fundamentally similar to those of retroviruses.